Alteration in sperm mitochondrial membrane potential and antioxidant biomarkers in summer adversely affects Hampshire-Ghungroo crossbred boar semen fertility in sub-tropical climate - Singh, Mahak; Celina, Apanai; Katiyar, Rahul; Deori, Sourabh; Singh, Ashwani; Singh, Vinay; Singh, G. D.; Rajoriya, J. S.; Kalita, H.; Mishra, V. K. (Frontiers in Veterinary Science, 2025)
In temperate regions, boars experience environmental heat stress due to the subtropical climate, leading to their semen quality and fertility being severely compromised compared to indigenous breeds. Considering the above effect, the present study aimed to evaluate the effect of season on semen quality, seminal plasma antioxidant status, and in vivo fertility of crossbred boars of exotic (50%) and indigenous inheritance in a subtropical climate. A total of 14 Hampshire–Ghungroo crossbred boars were used for this investigation, which took place in both summer and winter. Sperm characteristics, namely motility, viability, abnormality, acrosomal integrity, and the hypo-osmotic swelling test (HOST) results, and mitochondrial membrane potential (MMP) were evaluated. Sperm kinematics parameters were assessed using computer-assisted semen analysis (CASA). Antioxidant biomarkers (glutathione peroxidase, GPx; catalase, CAT; and total antioxidant capacity, TAC) and lipid peroxidation (malondialdehyde, MDA) were analyzed in boars’ seminal plasma. The summer season had a significant (p < 0.01) negative impact on reaction time and false mounts, whereas semen volume and sperm concentration were significantly (p < 0.01) higher in the winter season. Similarly, sperm abnormalities were significantly (p < 0.01) lower in the winter season. In the winter, sperm quality parameters, namely total motility, progressive motility, viability, acrosomal integrity, and HOST reactivity, were significantly (p < 0.01) improved. However, during the summer, sperm MMP was significantly (p < 0.01) lower in fresh samples and after 72 h of storage. Season had a significant (p < 0.05) effect on the following sperm kinematics parameters: average path velocity, straight-line velocity, curve linear velocity, amplitude of lateral head displacement, and beat cross frequency. Semen characteristics were significantly (p < 0.01) improved in winter after 72 h of cold storage compared with those in summer. The summer season had a significant effect (p < 0.01) on seminal plasma antioxidant biomarkers (TAC, MDA, CAT, and GPx). Furthermore, the farrowing rate was significantly (p < 0.05) higher in the winter season. In conclusion, our results showed that the low MMP of boar sperm and the downregulation of seminal plasma antioxidant biomarkers in summer lead to poor semen quality and poor fertility in Hampshire–Ghungroo crossbred boars in a subtropical climate. To alleviate the heat-stress-induced poor sperm fertility in boars and to optimize the fertility of boars during summer in subtropics, there is a need for scientific interventions in terms of genetics [less exotic inheritance (below 50%)], nutrition, and management.